Students’ Error Analysis in Solving Word Problems in Exponential Number Topic Based on Newman’s Error Analysis (NEA) Theory - Anita Ummu Hidayah; Sri Rejeki (EduMa: Mathematics education learning and teaching, 2022)
In mathematics, students usually experience errors in solving word problems. Previous studies found that students’ skills in solving word problems were not good enough. Therefore, exploring students’ errors to be a consideration in designing efforts to minimize these errors is necessary. This study aimed to describe the errors made by students in solving word problems in exponential numbers based on Newman’s theory. Based on Newman’s view, there are five stages of student error: reading errors, comprehension errors, transformation errors, process skill errors, and encoding errors. This research is a descriptive qualitative study involving grade nine with two students in each category, namely high, medium, and low levels of mathematics ability. The data collection was conducted through documentation and interview. The study’s data analysis involved data reduction, display, and conclusion drawing. Based on the data analysis, it could be concluded that: 1) students with high mathematical ability still committed errors in the transformation, process skill, and encoding stages, 2) students with moderate mathematical ability were still experiencing errors in the transformation, process skill, and encoding stages, but one of the subjects also made errors at the reading and comprehension stages, 3) students with the low mathematical ability experienced quite a lot of errors in solving the word problems, namely at the comprehension, transformation, process skill, and encoding stages but one of the subjects also made errors at the reading stage. These findings could be used as consideration in planning teaching and learning activities to minimize the occurrence of similar errors in students with various levels of mathematical ability.